Deictic Center Shifts in Literary Translation: the Spanish Translation of Nooteboom’s Het Volgende Verhaal - Goethals, Patrick; De Wilde, July (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractIn this article, we explore the phenomenon of deictic center shifts in literary translation, concentrating on the Spanish translation (La historia siguiente, 1992) of the Dutch novel Het volgende verhaal (1991 [The Following Story, 1993]). The empirical description focuses on lexical spatiotemporal markers and verbal tenses. We compare the source text and the target text in order to identify the translational shifts: we consider these shifts as textual traces of the translator’s interpretive process of resetting the spatiotemporal coordinates of the discourse. We will argue that the deictic shifts between source and target text are related to occasional hesitations of the translator, who tends to emphasize the most salient deictic center. On a methodological level, we hope to show that a close reading of a translated text, taking into account its thematic and structural peculiarities, can contribute both to Translation and Literary Studies.